Research in labor economics. Vol. 33 - Polachek, S. W.; Tatsiramos, Konstantinos; Akee, Randall K. Q. (Randall Kekoa Quinones); Edmonds, Eric V., 1971- (Bingley, U.K. : Emerald, 2011)
This volume contains nine original innovative chapters on worker well-being. Three chapters are on time allocated to work and human capital acquisition, three on aspects of risk in the earnings process, two on migration, and finally one on how tax policies affect poverty. Questions answered include: Are more educated women now opting out of work with a higher probability than in the past? Under what circumstances do young adults allocate non-school time to educational pursuits? How do macroeconomic shocks affect labor force participation rates? Can tax policies alleviate poverty? Are workers compensated adequately for taking risks? Do differences in private and public sector earnings affect mobility between the two sectors? And, do migrant parents affect educational decisions of their offspring?.
ch. 1. How do adolescents spell / Charlene M. Kalenkoski, David C. Ribar, Leslie S. Stratton -- ch. 2. The opt-out revolution : recent trends in female labor supply / Heather Antecol -- ch. 3. Female labor participation and occupation decisions in post-NAFTA Mexico / Rafael E. De Hoyos -- ch. 4. A risk augmented mincer earnings equation? : taking stock / Joop Hartog -- ch. 5. Workers' mobility and the return to education, evidence from public and private sectors / Yuval Mazar -- ch. 6. Foregone earnings from smoking : evidence for a developing country / Michael Lokshin, Kathleen Beegle -- ch. 7. The impact of worker effort on public sentiment toward temporary migrants / Gil S. Epstein, Alessandra Venturini -- ch. 8. Migrant networks, migrant selection, and high school graduation in Mico / Alfonso Miranda -- ch. 9. In-work transfers in good times and bad : simulations for Ireland / Olivier Bargain, Karina Doorley -- ch. 10. Exploring the determinants of employment in Europe : the role of services / Roberta Serafini, Melanie Ward.
Keywords: Labor economics